ECG SIGNAL RECOGNITION BASED ON WAVELET TRANSFORM USING NEURAL NETWORKS AND FUZZY SYSTEMS - ABDUL-RIDHA, HAIDER MEHDI; ALI, ABDULADHEM A. (Iraqi Journal for Electrical and Electronic Engineering, 2008)
This work presents aneural and fuzzy based ECG signal recognition system based on wavelet transform. The suitable coefficients that can be used as a feature for each fuzzy network or neural network is found using a proposed best basis technique. Using the proposed best bases reduces the dimension of the input vector and hence reduces the complexity of the classifier. The fuzzy network and the neural network parameters are learned using back propagation algorithm.